Ionic liquid‐based aqueous biphasic systems as a versatile tool for the recovery of antioxidant compounds. (31st October 2014) - Santos, João H.; e Silva, Francisca A.; Ventura, Sónia P. M.; Coutinho, João A. P.; de Souza, Ranyere L.; Soares, Cleide M. F.; Lima, Álvaro S.
<x xml:space="preserve">Abstract</x> The comparative evaluation of distinct types of ionic liquid‐based aqueous biphasic systems (IL‐ABS) and more conventional polymer/salt‐based ABS to the extraction of two antioxidants, eugenol and propyl gallate, is focused. In a first approach, IL‐ABS composed of ILs and potassium citrate (C6H5K3O7/C6H8O7) buffer at pH 7 were applied to the extraction of two antioxidants, enabling the assessment of the impact of IL cation core on the extraction. The second approach uses ABS composed of polyethylene glycol (PEG) and potassium phosphate (K2HPO4/KH2PO4) buffer at pH 7 with imidazolium‐based ILs as adjuvants. Their application to the extraction of the compounds allowed the investigation of the impact of the presence/absence of IL, the PEG molecular weight, and the alkyl side chain length of the imidazolium cation on the partition. It is possible to maximize the extractive performance of both antioxidants up to 100% using both types of IL‐ABS. The IL enhances the performance of ABS technology. The data puts in evidence the pivotal role of the appropriate selection of the ABS components and design to develop a successful extractive process, from both environmental and performance points of view. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:70–77, 2015